Research internship at Longwood Gardens in Kennett Square, Pennsylvania - Regan, Erin; Ferriss, Terry (My University, 2006)
Through a USDA Challenge Grant, tissue culture, Cedrus germination, and propagation of new plant material was researched at Longwood Gardens in Pennsylvania. Field trips to study the management structures of local gardens with the Longwood Graduate Fellows and Graduate Director Dr. Robert Lyons complemented the research activities.
Color poster with text describing research and work conducted by Erin Regan, advised by Dr. Terry Ferriss (University of Wisconsin-River Falls) during an internship at Longwood Gardens in Kennett Square, Pennsylvania. The internship involved working with tissue cultures of Cannas and Chrysanthemums, germination of Cedrus seeds, and propagation of a variety of different plants.
Keywords: Plant tissue culture; Chrysanthemums; Tissue culture; Plant propagation; Horticulture--Study and teaching(Internship); Plant evaluation; Cannas; Longwood Gardens (Kennett Square, Pa.); Plant germination; Cedrus; Horticulture